Biologia populacional do camarão explorado comercialmente Artemesia longinaris (Decapoda: Penaeidae) em uma região de ressurgência do Atlântico Ocidental: Comparação em diferentes latitudes - Sancinetti, G. S. [UNESP]; Azevedo, A.; Castilho, A. L. [UNESP]; Fransozo, A. [UNESP]; Costa, R. C. [UNESP] (FapUNIFESP (SciELO), 2015)
This study characterized the population biology of the dendrobranchiate penaeid shrimp Artemesia longinaris Spence Bate, 1888, focusing on population structure, sexual maturity, reproductive period and recruitment, and comparing reproductive parameters of a different populations along western South Atlantic..Samples were collected monthly from March, 2008 to February, 2010 in Macaé, northern coast of Rio de Janeiro State, Brazil, a region influenced by the Cabo Frio upwelling. There was a significantly higher percentage of females and with larger sizes than males. Both carapace length and sexual maturity in Macaé were similar to the dimensions found in populations in the South of the continent (Argentina). Reproductive females were present in all months, with main peaks during winter and summer. Recruitment was also continuous, with peaks, usually one to two months after the appearance of reproductive females, after the reduction of the bottom temperature values of water. These data suggest that November to January would be the appropriate months for legal off-season, due to the higher intensity of spawning females and juveniles during this period. A comparação latitudinal dos parâmetros reprodutivos, não confirma o paradigma de que tamanho do corpo e a maturidade sexual das fêmeas são menores em regiões tropicais e aumentam em direção às maiores latitudes, reforçando a hipótese da influência e importância da ACAS na dinâmica reprodutiva de A. longinaris na região The results of this study contribute to the understanding of the biology of A. longinaris, and could also be a reference to monitor this important fishery resource and consequent legal off-season. Furthermore, this population located at the northern limit of the species distribution is a source of highly relevant comparison for population studies in other areas.
Population biology of the commercially exploited shrimp Artemesia longinaris (Decapoda: Penaeidae) in an upwelling region in the western Atlantic: Comparisons at different latitudes
Keywords: Dendrobranchiata; Recruitment; Reproductive biology; Sex ratio; Shrimp fishery